1991
DOI: 10.1172/jci115216
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in skin collagen glycation with improved glycemic control in patients with insulin-dependent diabetes mellitus.

Abstract: Glycation, oxidation, and nonenzymatic browning of protein have all been implicated in the development of diabetic complications. The initial product of glycation of protein, fructoselysine (FL), undergoes further reactions, yielding a complex mixture of browning products, including the fluorescent lysine-arginine cross-link, pentosidine. Alternatively, FL may be cleaved oxidatively to form Nf-(carboxymethyl)lysine (CML), while glycated hydroxylysine, an amino-acid unique to collagen, may yield N4-(carboxymeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 31 publications
8
74
0
3
Order By: Relevance
“…The data support the assumption that the formation of collagen FL is in equilibrium with ambient glucose concentrations [5]. Glycation alone may have a pathogenic role in the development of diabetic complications, and collagen FL is a predictor of complications in DCCT subjects [21,22].…”
Section: Collagen Glycation Glycaemic Control and Complicationssupporting
confidence: 77%
See 3 more Smart Citations
“…The data support the assumption that the formation of collagen FL is in equilibrium with ambient glucose concentrations [5]. Glycation alone may have a pathogenic role in the development of diabetic complications, and collagen FL is a predictor of complications in DCCT subjects [21,22].…”
Section: Collagen Glycation Glycaemic Control and Complicationssupporting
confidence: 77%
“…It has been suggested that collagen glycation may directly reflect cumulative glycaemia for at least 1 year before measurement [21]. However, our earlier study of type 1 diabetic patients showed that 4 months of intensive therapy decreased skin collagen FL by 25%, while having no effect on levels of collagen AGEs [5].…”
Section: Collagen Glycation Glycaemic Control and Complicationsmentioning
confidence: 69%
See 2 more Smart Citations
“…This may, in part, explain the W. G. JOHN AND E. J. LAMB failure to observe a decrease in skin collagen pentosidine following institution of improved glycaemic control in diabetics. 40 Alternatively, Baynes41 has suggested that pentosidine is the result of an oxidative reaction between lysine and arginine. In addition to these AGE products, two further pyrrole-related compounds have been described and structures proposed.…”
Section: Biochemistry Of the Late Maillard Reactionmentioning
confidence: 99%